Bacterial and Fungal Communities Are Differentially Modified by Melatonin in Agricultural Soils Under Abiotic Stress - Madigan, Andrew P.; Egidi, Eleonora; Bedon, Frank; Franks, Ashley E.; Plummer, Kim M. (Frontiers in Microbiology, 2019)
An extensive body of evidence from the last decade has indicated that melatonin enhances plant resistance to a range of biotic and abiotic stressors. This has led to an interest in the application of melatonin in agriculture to reduce negative physiological effects from environmental stresses that affect yield and crop quality. However, there are no reports regarding the effects of melatonin on soil microbial communities under abiotic stress, despite the importance of microbes for plant root health and function. Three agricultural soils associated with different land usage histories (pasture, canola or wheat) were placed under abiotic stress by cadmium (100 or 280 mg kg-1 soil) or salt (4 or 7 g kg-1 soil) and treated with melatonin (0.2 and 4 mg kg-1 soil). Automated Ribosomal Intergenic Spacer Analysis (ARISA) was used to generate Operational Taxonomic Units (OTU) for microbial community analysis in each soil. Significant differences in richness (α diversity) and community structures (β diversity) were observed between bacterial and fungal assemblages across all three soils, demonstrating the effect of melatonin on soil microbial communities under abiotic stress. The analysis also indicated that the microbial response to melatonin is governed by the type of soil and history. The effects of melatonin on soil microbes needs to be regarded in potential future agricultural applications.